ARAHAN PENGEMBANGAN LAHAN UNTUK PADI SAWAH DI KABUPATEN BANDUNG BARAT, JAWA BARAT - Asep Anwar Nugraha; Widiatmaka Widiatmaka; Irman Firmansyah (Tataloka, 2019)
Rice is still a staple food in Indonesia, including in West Bandung Regency West Java Province. West Bandung regency was reached food self-sufficiency in 2010. The objectives at this study were: i) to identify land use land cover (LULC) in West Bandung; ii) to analyze suitability and availability for paddy field in West Bandung and iii) to arrange the direction of rice field development in West Bandung. Data analysis using geografis information system (GIS). Identify land use land cover by interpretation of SPOT imagery 6 2016. Analysis of the suitability and availability of paddy fields by overlapping land use maps, maps of forest areas and soil maps. The direction of paddy fields development based on actual land and a potential land of paddy fields. The alignment of wetland land use by overlapping maps of suitability and availability of land and spatial pattern patterns (RTRW) Kabupaten Bandung Barat 2009-2029. The result of land use interpretation is dominated by forest area of 37,335 ha, while paddy field area 15,953 ha. Land suitability evaluation consists of suitable (S2) and marginally suitable (S3) using matching criteria. The analysis result shows that the land suitability and available for paddy field was 25,147 ha. Direction of land development for Paddy field area was directed to actual paddy field largely 14,923 ha for intensification and potential land available for paddy field largely 10,224 ha for extensification. The land use of paddy fields has alignment with RTRW covering 2,018 ha and recommended as sustainable food agriculture land.